Rekonstruksi Fikih Informasi terhadap Deepfake Keagamaan di Era Artificial Intelligence: Pendekatan Maqāṣid al-Syarī‘ah - Zulfikar Fikar; Nashrul Mu’minin; Mila Kamelia Putri (Bidang Penelitian Dan Penulisan Karya Ilmiah (bp2ki) Ma'had Aly Lirboyo, 2026)
The rapid development of artificial intelligence technology has accelerated the emergence of deepfake-based religious content capable of manipulating audio, visual, and narrative representations of religious authorities in digital spaces. This phenomenon raises serious concerns regarding the authenticity of Islamic information, the credibility of religious authorities, and the increasing spread of epistemic disinformation among Muslim societies. Existing Islamic legal studies predominantly focus on general digital ethics and online misinformation, while the specific issue of religious deepfakes remains insufficiently examined within the framework of Islamic jurisprudence. This study aims to reconstruct the concept of fiqh al-maʿlūmāt (Islamic information jurisprudence) in responding to religious deepfakes through the perspective of maqāṣid al-sharī'ah. This research employs normative legal research through library study with conceptual and maqāṣid approaches, and descriptive-analytical data analysis. The findings reveal that religious deepfakes contain elements of tadlīs, gharar al-maʿlūmāt, and epistemic mafsadah that threaten the principles of ḥifẓ al-dīn, ḥifẓ al-ʿaql, and ḥifẓ al-ʿirḍ. This study argues that maqāṣid al-sharī'ah should function as an ethical and legal foundation for developing verification mechanisms, digital religious authority, and Islamic artificial intelligence governance. The research contributes to the development of contemporary Islamic legal discourse concerning digital information ethics in the era of artificial intelligence.